A Qualitative Study of Referral Back Programme Implementation in Palembang Health Centres for Chronic Disease - hasyim, hamzah; Amayu, Rizka; Syakurah, Rizma Adlia; Misnaniarti, Misnaniarti; Windusari, Yuanita; Novrikasari, Novrikasari (BPJS Kesehatan, 2025)
Despite the strategic intent of Indonesia’s National Health Insurance (NHI) to strengthen chronic disease management through the Referral Back Programme (PRB), its implementation at primary health centres (Puskesmas) continues to face operational and systemic barriers. This study aimed to analyse the implementation of the PRB for chronic non-communicable diseases in Palembang City. The research team employed a qualitative case study approach to explore key challenges in programme execution. The research team collected data from six purposively selected Puskesmas between July and September 2022, using in-depth interviews, focus group discussions, observations, and document reviews. They selected twenty-one informants—including BPJS Kesehatan officials, physicians, programme coordinators, and patients—using maximum-variation sampling to ensure diverse stakeholder representation. The team conducted a thematic analysis, identifying three key themes. First, organisational capacity constraints, such as staff shortages, dual workloads, inadequate training, and limited funding. Second, there are infrastructural and systemic barriers, including the lack of dedicated service corners, underdeveloped digital systems, medicine stockouts, and restricted distribution of referral tools. Third, communication and coordination gaps exist, including weak inter-agency reporting, inadequate feedback mechanisms, and limited outreach to JKN participants. These themes align with the input–process–output framework: input barriers reflected fragmented resources; process barriers involved absent guidelines and reactive supervision; output challenges included low patient adherence and insufficient reporting. These interlinked factors undermine the gatekeeping function of Puskesmas and disrupt the continuity of care for chronic conditions. Strengthening institutional capacity, aligning resources, and integrating digital infrastructure are crucial for enhancing the effectiveness and sustainability of the PRB, thereby supporting Indonesia's progress toward universal health coverage.